Electromagnetic processes - Gould, Robert J. 1935- (Princeton series in astrophysics., 2006)
This book provides an understanding of the theoretical foundations for the calculation of electromagnetic processes. Photon production processes are particularly important in astrophysics, since almost all of our knowledge of distant astronomical objects comes from the detection of radiation from these sources. Further, the conditions therein are extremely varied and a wide variety of naturally occurring electromagnetic phenomena can be described by limiting forms of the basic theory. The first chapter reviews some basic principles that are the underpinnings for a general description of electromagnetic phenomena, such as special relativity and, especially, relativistic covariance. Classical and quantum electrodynamics (QED) are then formulated in the next two chapters, followed by applications to three basic processes (Coulomb scattering, Compton scattering, and bremsstrahlung). These processes are related to other phenomena, such as pair production, and the comparisons are discussed. A unique feature of the book is its thorough discussion of the nonrelativistic limit of QED, which is simpler than the relativistic theory in its formulation and applications. The methods of the relativistic theory are introduced and applied through the use of notions of covariance, to provide a shorter path to the more general theory. The book will be useful for graduate students working in astrophysics and in certain areas of particle physics.